ACTION RESEARCH HYPNOTHERAPI PADA PENANGANAN NYERI DAN KECEMASAN PASIEN KANKER KOLON - Sakiyan Sakiyan (Fakultas Ilmu Kesehatan, 2014)
Based Permenkes RI. No. 1109 of 2007 legalized complementary therapies carried out in health facilities, Permenkes RI No. HK.02.02 / Menkes / 148/1/2010 on the Implementation of License and Nurse Practice, hypnotherapy has become a complementary therapy used by nurses. Qualitative research design was used with action research approach to implement the method hypnotherapy. The study population was patients who had undergone colon cancer surgery and is undergoing chemotherapy who experience pain and anxiety. The study was conducted for 6 weeks in the Banyumas General Hospital, with purposive sampling technique gained 6 participants. The research instrument used in-depth interviews and participant observation after getting the hypnotherapy intervention. Data processing and data interpretation using NVivo software 9.0.204.0. research shows the level of pain and anxiety hypnotherapy respondents declined after 1-3 cycles, the average decrease in pain every cycle between 4 to 6.3, while the average decrease anxiety decrease between 7 to 15.8. Conclusions in hypnotherapy research helpful in reducing pain and anxiety of patients who suffer from colon cancer and is undergoing chemotherapy in Banyumas General Hospital. Keywords: hypnotherapy, colon cancer, pain, anxiety.